RANCANGAN SENSOR PERGESERAN TANAH BERBASIS SERAT OPTIK UNTUK DETEKSI LONGSOR: STUDI AWAL (Measurement of Curvature Optical Fiber Loss As A Displacement Sensors In Landslide Detector) - Wildan Panji Tresna; Dwi Hanto; Bambang Widiyatmoko (Widyariset, 2010)
The optical extensometer based optical fiber have been designed by Single Mode Optical Fiber with the basic component are light, optical fiber in circling condition and photodetector. Early experiment have been carried out loss optical fiber curvature of the correlation factor of a circle diameter of the displacement. Measurement results showed differences to laser intensity at the position of the optical fiber is straight and the position make to curve. Measurement made on the condition R1 = 18.7 mm as L1 = 0 mm until R2 = 15.6 mm as L2 = 9 mm. The working principles of equipment that is create when a laser through optical fiber missed in the curve and pull up to a certain frictions the loss geometry would be the bigger.